Typological Classification of the Cyrillic Manuscripts and Early Printed Books with the Gospel Texts - Ostapczuk, Jerzy (Studia Ceranea, 2016)
The paper presents the rules for typological classification of Slavonic manuscripts and early printed books with the Gospel text. It enumerates different types of the books with the Gospel and sometimes also with other parts of the Holy Scripture. Information about the Greek tradition of the Gospel is also included in the article and serves as the basis of comparison.